Do COFAS Scores Effect the Outcomes of a 4th Generation Total Ankle Prosthesis? A 2-Year Follow- Up. Issue 4 (November 2022) - Gross, Christopher E.; Strasser, Nicholas L.; Friscia, David A.; Vora, Anand M.; Doty, Jesse F.
Category: Ankle Arthritis; Ankle Introduction/Purpose: Fourth generation ankle replacements benefit from improved surgical technique, respect for bony preservation, and increased surgeon awareness of operative indications. In order to better compare and stratify pre-operative ankle arthritis patients, the Canadian Orthopaedic Foot and Ankle (COFAS) pre-operative classification for end-stage ankle arthritis score was developed. The purpose of this study is report on how the COFAS scores effects prospectively collected patient reported outcome measures(PROMs) in a multi-institutional study of a fourth-generation total ankle replacement. Methods: Patients presenting for a total ankle replacement at 9 institutions were prospectively enrolled and implanted in both academic and private settings. Each patient received an INFINITY ankle prosthesis (Stryker, Memphis, TN, USA). Patients had their COFAS pre-operative classification for end-stage ankle arthritis scores, and PROMs recorded pre-operatively and at 6 months, 12 months, and 24-month intervals. The following PROMs were collected: Ankle Osteoarthritis Score (AOS), PROMIS Global Physical Health, and Foot and Ankle Outcome Score (FAOS). The preoperative and latest follow-up scores for patients with two years of follow-up were analyzed. Results: A total of 147 patients were prospectively enrolled. for study participation. COFAS types; were delineated as Type 1 (42.6%, isolated ankle arthritis), Type 2 (27.0%, ankle arthritis with varus or valgus deformity, tight Achilles, ankle instability), Type 3(4.7%, ankle arthritis with hindfoot deformity, tibial malunion), and Type 4 (25.8%, Types 1-3, plus hindfoot arthritis). Eighty-eight (88) patients had at least 24 months of follow-up. COFAS Types 1, 2, 3, and 4 patients had significant improvements in all domains of the AOS, PROMIS, and FAOS Scores (p<0001). The type and severity of deformity or amount of hindfoot arthritis, hindfoot deformity, or ankle instability significantly effected the PROMs in those patients with at least 2-year follow-up. Implant revision rates were not affected by COFAS type, and there were three revisions (One Type 4 and two Type 2). Conclusion: At two-year follow-up, all study participants had significant improvements in PROMs, regardless of COFAS Type. These results suggest that COFAS type has little impact on patient outcomes using current generation total ankle replacements. Longer term follow-up may serve to further confirm these promising early results.